Ai’s (re)place In Pre-service Teacher Training. A Case Study On Teaching And Learning Foreign Languages - Pop, Raluca; Marc, Anamaria (The Journal of Studies in Language, Culture, and Society, 2025)
Due to the rapid advances in technology, the integration of artificial intelligence (AI) tools in educational settings presents a transformative opportunity to promote personalized learning experiences. However, at the same time, it also raises significant ethical concerns. Educators are called upon to redefine their teaching roles in the triad represented by sound subject matter knowledge, pedagogical knowledge and digital competence. Furthermore, they must develop procedural knowledge to critically explore, from a didactic perspective, the multifaceted opportunities and challenges associated with incorporating AI tools into formal educational environments. This study investigates pre-service teachers’ perspectives on the use of AI in learning and teaching a foreign language. Undergraduate students enrolled in vocational teacher training represent a new generation of educators who navigate the ethical dilemmas connected to AI-generated content. These would-be teachers are expected to facilitate the knowledge acquisition process for Alpha Generation students, who expect new communication technologies to be part of their daily routine. Thus, the stakes for the teaching profession are high as pre-service teachers’ professional development undergoes significant transformation shaped by technological advancements. The study included 52 participants and employed two research instruments: a survey and a semi-structured interview. Data collected with the survey were analysed qualitatively and quantitatively through descriptive statistics using Google Forms’ built-in tools and Voyant Tools for content analysis. Data from the semi-structured interview were also analyzed with Voyant Tools. The study contributes to the existing literature on the topic of understanding pre-service teachers’ opinions on integrating AI in teaching foreign languages, thereby broadening the educational landscape shaped by AI.